APPRAISAL ANALYSIS OF CHARACTERIZATION OF THE MAIN CHARACTER IN PRAMOEDYA ANANTA TOER'S NOVEL IN INDONESIAN AND ENGLISH TRANSLATION OF THIS EARTH OF MANKIND - Jafar Sodiq; Theresia Cicik Sophia Budiman; Nur Hidayat (Universitas PGRI Semarang, 2022)
The number of Indonesian novels translated into various foreign languages, especially English, requires a deeper study so that illegibility and unacceptableness will not occur in conveying the true meaning in the source language. This study examines the disclosure of the main character in the novel Bumi Manusia by Pramoedya Ananta Toer which was translated into English This Earth of Mankind using Appraisal theory in Functional Systemic Linguistics (LSF) perspective which includes the culture of the source language in it. The results of the analysis show that there is a shift in appraisal or a shift in the type of appraisal in the depiction of the main character in the novel in the source language (Indonesian) with the depiction of the character in the target language (English) as seen in the change in the choice of expression (words or phrases) in the target language. This can be interpreted that in the world of translation, the choice of equivalent target language words will always change according to acceptance with the culture and norms that apply to the target language.